ECOLOGICAL ENERGETICS OF TROPICAL LIMPET Cellana testudinaria (Linnaeus, 1758) LIVING ON THE ROCKY SHORE OF OHOIWAIT, SOUTHEAST MOLUCCAS, INDONESIA - Abraham S Khouw (JOURNAL OF COASTAL DEVELOPMENT, 2008)
Study on ecological energetics of tropical limpet C. testudinaria has been carried out at approximatelyone year from October 2001 to September 2002. Population energy budgets estimated on theassumption of steady state conditions for C. testudinaria (Linnaeus, 1758) on the rocky shore ofOhoiwait, are presented. Large difference in population structure, and hence energetics, occurred atdifferent localities along the rocky shore. Relatively high proportions (98 %) of the assimilated energywas lost via metabolism. Assimilation efficiency is 39 %, net growth efficiency is 1.8 %, and ecologicalefficiency 0.3 %. Production (P), energy flow (A) and total energy consumption (C) were expressed asfunctions of animal size, in order to facilitate gross estimations of the energy component for which dataon size frequency and density are available.